Analysis of the business model elements and their relationships - Fliegner, Wojciech (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Business model that articulates the economic logic of how an organization creates and delivers value should underlie every performance measurement system and should explain how the important nonfinancial and financial variables in the performance measurement system are related to each other. Due to the lack of research in this area, the conceptual framework for analyzing elements of the business model and relations between them has been proposed. This paper explores also the concept of business model life cycle and controlling as a part of this concept. For analysis of business models this study proposes resource and process consumption accounting (RPCA) method. Its components (resources, activities, products/services, customers) are at the same time elements associated with the Osterwalder’s Business Model Canvas (BMC)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 53-64
Keywords: business model life cycle; resource and process consumption accounting; cykl życia modelu biznesowego; zasobowo-procesowy rachunek kosztów